2004
DOI: 10.1016/j.physa.2003.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Power law for the calm-time interval of price changes

Abstract: In this paper, we describe a newly discovered statistical property of time series data for daily price changes. We conducted quantitative investigation of the calm-time intervals of price changes for 800 companies listed in the Tokyo Stock Exchange, and for the Nikkei 225 index over a 27-year period from January 4, 1975 to December 28, 2001. A calm-time interval is defined as the interval between two successive price changes above a fixed threshold. We found that the calm-time interval distribution of price ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…Whereas the second class of behavior has been observed in the response times of Einstein's and Darwin's corrependence [16]. Finally, the third class of behavior has been observed in earthquakes and the stock exchange [9,10,11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the second class of behavior has been observed in the response times of Einstein's and Darwin's corrependence [16]. Finally, the third class of behavior has been observed in earthquakes and the stock exchange [9,10,11,12].…”
mentioning
confidence: 99%
“…In the case of the stock exchange [10], it was shown that the scaling exponent tends to decrease as the threshold on the normalized fluctuations increases. In other words, when waiting times between large fluctuations are considered, the scaling exponent approaches α = 1 indicating possibly a different mechanism like a queue model [21] or a power-law injection, whereas when small variations are considered the exponent is close to α = 2, which could be a signature of seasonality [9] or uncorrelated probability variations.…”
mentioning
confidence: 99%
“…"silent" or "calm") periods [23]. Such a behaviour has been independently verified by Kaizoji et al [24].…”
Section: Introductionmentioning
confidence: 62%
“…A lot of researchers have found that such as web browsing [1], [5], blog comments [6], market trading [7], human communication behavior [8]- [10], logistics transportation [11] and other human behavior all obey the power law relationship .Therefore, many researchers studied the method to determine whether a distribution is a power law distribution and an estimate of the power exponent.…”
Section: Methodsmentioning
confidence: 99%